1 answer:
X + 2y = 3 Solve the Equation
- 2y -2y
x = 3 - 2y
5x + 3y = 8
5(3 - 2y) + 3y = 8 Substitute x
15 - 10y + 3y = 8 Combine Like Terms
15 - 7y = 8
-15 -15
-7y = -7
Divide 7 from y (Do on both sides)
y = 1
x = 3 - 2(1) Substitute y
x = 3 - 2
x = 1
(X, Y) = (1, 1)
You might be interested in
Answer:
b
Step-by-step explanation:
Answer:
f=42
fdb=104
Step-by-step explanation:
Answer:
i dot kniw
Step-by-step explanation:
Answer:
Step-by-step explanation:
1+2
+2v+4
Answer:5,6 or 15,2
5x6x1.5 =45
15x2x1.5=45